2019
DOI: 10.3390/s19245444
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-Online BMI Based on EEG to Detect the Appearance of Sudden Obstacles during Walking

Abstract: The aim of this paper is to describe new methods for detecting the appearance of unexpected obstacles during normal gait from EEG signals, improving the accuracy and reducing the false positive rate obtained in previous studies. This way, an exoskeleton for rehabilitation or assistance of people with motor limitations commanded by a Brain-Machine Interface (BMI) could be stopped in case that an obstacle suddenly appears during walking. The EEG data of nine healthy subjects were collected during their normal ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…In many online BCI systems, IMUs are used to measure the real movement to ensure smooth operation. Elvira et al ( 2019 ) placed 7 IMUs on lumber, thigh, shin, and foot to measure the actual movement to detect stop intention. IMUs serve as feedback to ensure the real physical stop.…”
Section: Hybrid Eeg-fnirs-based Bcimentioning
confidence: 99%
See 2 more Smart Citations
“…In many online BCI systems, IMUs are used to measure the real movement to ensure smooth operation. Elvira et al ( 2019 ) placed 7 IMUs on lumber, thigh, shin, and foot to measure the actual movement to detect stop intention. IMUs serve as feedback to ensure the real physical stop.…”
Section: Hybrid Eeg-fnirs-based Bcimentioning
confidence: 99%
“…Due to LDA's simplicity and effectiveness, it is widely used in the classification of EEG and fNIRS signals for gait disorders (Bulea et al, 2014 ; Rea et al, 2014 ; Salazar-Varas et al, 2015 ; Naseer et al, 2016 ; Gui et al, 2017 ; Khan R. A. et al, 2018 ; Costa-Garciacutea et al, 2019 ; Elvira et al, 2019 ). Fazli et al ( 2012 ) used LDA to classify MI tasks and found that simultaneous EEG-fNIRS measurement helped increase the classification accuracy by 5%.…”
Section: Hybrid Eeg-fnirs-based Bcimentioning
confidence: 99%
See 1 more Smart Citation
“…In upper-limb rehabilitation, the physiological interaction of the patient with the robotic device is critical. In [7], two different physiological control methods based on EEG and electrooculography (EOG) are evaluated, while measuring stress levels from skin conductance level (SCL) and heart rate variability (HRV). This study shows that EEG control is associated with a higher level of stress and mental workload when compared to EOG control.…”
Section: Contributionsmentioning
confidence: 99%
“…Dimensionality reduction is very important, because it alleviates undesired properties of high-dimensional spaces, such as "the curse of dimensionality" [5]. In the literature, various dimensionality reduction methods have been proposed: (i) linear methods, such as principal component analysis (PCA) [6,7] and linear discriminant analysis (LDA) [8,9], and (ii) nonlinear methods, such as isometric mapping (ISOMAP) [10,11] and the non-parametric version of t-distributed stochastic neighbor embedding (t-SNE) [12].…”
Section: Introductionmentioning
confidence: 99%